Teachers' Perspectives on the Use of Basic Mathematical Operations Skills Modules for Dyscalculia Students - Liang Soon, Vestly Kong; Salim, Mardiana; Peng Chong, Ai (Semarak International Journal of STEM Education, 2024)
Some pupils struggle with math due to dyscalculia, a condition that makes learning and working with numbers difficult. As agents of 21st-century education, teachers play a crucial role in applying student-centered, engaging methods to support these pupils effectively. To enhance our understanding of how to effectively support dyscalculic students, this study explores teachers' perspectives on the use of specialized modules for basic mathematical operations. The thoughtfully designed module aims to provide a structured and visually engaging learning experience, specifically tailored to address the unique challenges faced by students with dyscalculia. The design of this study uses qualitative approaches by using semi-structured interviews and observations to determine how the modules are used to teach basic arithmetic operations to dyscalculic students, verify whether the use of these modules would help dyscalculic students catch up with their peers in math performance, and find out teachers' barriers with handling the modules. The study sample consisted of three special education mathematics teachers. The findings show all of the three respondents use the basic mathematical operations skills module for dyscalculic students weekly during math lessons. Results indicate that providing modules tailored to the abilities and needs of dyscalculic students is crucial for overcoming their math difficulties. This study also reveals an effective strategy when students struggle in math. However, one of the most important challenges special education math teachers is the problem of student attendance. Nevertheless, research involving the mathematical skills of dyscalculia students can be further improved by looking for the development of teaching and learning of special education teachers and students. The implications of this paper are significant, offering a foundation for designing models and modules tailored for dyscalculic students and developing suitable instruments to enhance their learning experience.